OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) DARI RETRIBUSI PASAR KOTA PEKANBARU - Indra Safri; Ahmad Rivai; Rendra Wasnury; Afridayanti Afridayanti (VALUTA, 2019)
The Study on Optimizing Original Local Government Revenue (PAD) from the Market Levy was determined the potential of Original Local Government Revenue (PAD) from the traditional market levies owned by the Pekanbaru City Government. In general, the purpose of this activity was to collect data, using a survey method for data collection of Stalls and Street Vendors that exist in the traditional markets of the Pekanbaru City Government. Optimizing the acquisition of PAD from traditional market retribution in the city of Pekanbaru is Rp. 566,643,000 per year if the estimated traditional market levies planned for 2019 have included cleaning levies on the market. If only the estimated revenue obtained from the levies on the use of market service facilities in the form stalls and street vendors only (not included in the 2019 DISPERINDAG cleanliness estimate) then there is Rp. 940,863,000 per year as a retribution that can be optimized. To increase market retribution revenue, some concrete steps are needed. Firsly, to increase collection efficiency, namely by reducing unnecessary costs where the percentage of collection fees is lowered or smaller than the percentage increase in revenue realization so that from year to year market levies show an increase in efficiency. Moreover, revise Perda No. 8 of 2017 concerning market service levies by providing explicit delegation to the OPD relating to the market to fully manage the market both for cleanliness and parking lots